Penerapan Model Pembelajaran Discovery Learning Menggunakan Roket Air pada Materi Momentum dan Impuls untuk Meningkaatkan Motivasi Belajar Siswa di SMA Negeri 1 Batang Natal - Aslamiyah Rambe; Ainun Mardiyah Lubis; Fitri Agustina Lubis; Syahruddin Aritonang; Arbaiyah Arbaiyah (Journal on Education, 2023)
The problem this study is the lack of motivation to learn students due to lack of interaction between students and teachers. To overcome this problem, applied a discovery learning model using water rockets. The purpose of this study was to increase students' motivation to learn. This type of research is classroom action research (CAR) conducted in two cycles. Each consists of four stages, namely planning, action, observation, and reflection. This research was carried out in 1 Batang Natal State High School. The subjects of this study were students of class X MIA1. The technique used in data collection is tests, questionnaires and observations and data collection tools is learning outcomes tests, learning motivation questionnaires, and observation sheets of learning activities. The results of student learning tests that were completed in the first cycle were 21.73% and in the second cycle was 82.60%.The results of student physics learning motivation questionnaires in the first cycle of 56.85% and in the second cycle amounted to 79.71%. Can be concluded that this study has been successful and learning Discovery learning using water rockets can be used in the teaching and learning process.